The Long Non-coding RNA lnc-DMP1 Regulates Dmp1 Expression Through H3K27Ac Modification - Xin Xia (Frontiers in Genetics, 2020)
Several long non-coding RNAs (lncRNAs) have been reported regulate the expression of neighbor protein-coding genes at post-transcriptional, transcriptional and epigenetic levels. Dmp1 (Dentin matrix protein 1), encoding a non-collagenous extracellular matrix protein, plays an important role in dentin and bone mineralization. However, the transcriptional regulation of lncRNA on Dmp1 has not been reported. In this study, we identified a novel lncRNA named lnc-DMP1, which is near the Dmp1 gene region and undergoes remarkable changes during mandible development. lnc-DMP1 is co-localized and significantly expressed correlation with Dmp1 in embryonic and postnatal mouse mandibles. In MC3T3-E1 cells, lnc-DMP1 positively regulates DMP1 expression and skeletal mineralization. Furthermore, lnc-DMP1 induces the promoter activity of Dmp1 by modulating H3K27Ac enrichment in the Dmp1 promoter. In conclusion, our results indicate that lnc-DMP1 is a novel lncRNA near the Dmp1 gene region and regulates Dmp1 expression by modulating the H3K27 acetylation level of Dmp1 promoter.